Aplikasi Waste Assessment Model (WAM) Pada Proses Perencanaan Anggaran Menggunakan Sistem SILUNA - Lusiani, Ni Wayan; Sudarma, Made; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i01.P04, 2023)
Implementing an audit process is one way to raise the quality of both products and processes. Detecting the presence of waste is one of the audit procedures that can be used. Waste is a behavior in and of itself that adds no value. Lean is the auditing technique used to find waste. Lean primarily focuses on identifying and removing non-value-added activities. Lean has a mechanism for identifying waste in its implementation, and that method is the Waste Assessment Model (WAM). In the Planning Section of the Planning and Finance Bureau of Udayana University, the application of WAM is concentrated on planning to identify waste in the budget process utilizing the SILUNA system. The findings of this study can be summarized as follows: defect is the largest waste with a proportion of 19,79%; inventory are the second sequence of waste with a proportion of 16,35%. Key Word— Lean; Waste; Waste Assessment Model